Transposable elements mark a repeat‐rich region associated with migratory phenotypes of willow warblers (Phylloscopus trochilus). Issue 4 (5th December 2021) - Caballero‐López, Violeta; Lundberg, Max; Sokolovskis, Kristaps; Bensch, Staffan
Abstract: The genetic basis of bird migration has been the focus of several studies. Two willow warbler subspecies ( Phylloscopus trochilus trochilus and Phylloscopus trochilus acredula ) follow different migratory routes to wintering grounds in Africa. Their breeding populations overlap in contact areas or "migratory divides" located in central Scandinavia and in eastern Poland. Earlier analyses demonstrated that the genetic differences between these two migratory phenotypes are few and cluster on chromosomes 1 and 5. In addition, an amplified fragment length polymorphism‐derived biallelic marker (known as WW2) presents steep clines across both migratory divides but failed to be mapped in the genome. Here, we characterize the WW2 marker and describe its two variants (WW2 ancestral and WW2 derived) as portions of long terminal repeat retrotransposons originating from an ancient infection by an endogenous retrovirus. We used quantitative polymerase chain reaction techniques to quantify copy numbers of the WW2 derived variant in the two subspecies and their hybrids. This, together with genome analyses revealed that WW2 derived variants are much more abundant in P . t . acredula and appear embedded in a large repeat‐rich region (>12 Mbp), not associated with the divergent regions of chromosomes 1 or 5. However, it might interact with genetic elements controlling migration direction. Testing this hypothesis further will require knowing the exact location of this region, such as by obtaining more complete genome assemblies preferably in combination with techniques like fluorescence in situ hybridization applied to a willow warbler karyotype, and finally to investigate the copy number of this marker in hybrids with known migratory tracks.